1995
DOI: 10.1111/j.1467-8659.1995.cgf143_0159.x
|View full text |Cite
|
Sign up to set email alerts
|

Thoughtful Drawings: A Computational Model of the Cognitive Nature of Children's Drawing

Abstract: An interpretation of children's drawing is presented that is based on active perception of the world and the construction of an equivalent self contained two‐dimensional world. This model is implemented in a computer program called Rose (Representation Of Spatial Experience). Inspired by the drawings of young children, Rose simulates the perception of the general form and structure of three‐dimensional computer models and constructs equivalent childlike two‐dimensional representations from them. Rose serves to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Stick figures are also used by infants and primitive cultures in early representations of human or animal forms. A computational system based on generalized cylinders called ROSE (Representation Of Spatial Experience) was developed in the mid-1990s by (Burton, 1995) to model young children's drawing.…”
Section: Visual Arts: Painting Drawing Sculptingmentioning
confidence: 99%
“…Stick figures are also used by infants and primitive cultures in early representations of human or animal forms. A computational system based on generalized cylinders called ROSE (Representation Of Spatial Experience) was developed in the mid-1990s by (Burton, 1995) to model young children's drawing.…”
Section: Visual Arts: Painting Drawing Sculptingmentioning
confidence: 99%
“…In automatic surface shading to produce illustrations and engravings, Deussen et al use the 3D MA to provide the main axial directions from which to derive perpendicular intersection planes to draw hatching strokes on the object's surface (Deussen et al, 1999). A computational system based on generalized cylinders connected via an MA graph, named ROSE (Representation Of Spatial Experience), was developed in the mid-1990s by Ed Burton to model young children's drawings (Burton, 1995).…”
Section: Use Of the Ma In Computerized Drawing Systemsmentioning
confidence: 99%
“…Kennedy [10] let blind individuals draw spatial scenes and concluded that they do not represent images with perspective, maintaining a flat bidimensional projection in their drawings. Burton developed a system called Rose [3] that imitates children's drawings based on spatial models. However until now no systematic approach has been developed to design perceptual image maps of three-dimensional objects and scenes without visual cues.…”
Section: Introductionmentioning
confidence: 99%